2004
DOI: 10.1111/j.1365-2044.2004.03736.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of bispectral index during a cardiopulmonary arrest: a potential predictor of cerebral perfusion

Abstract: SummaryA 62-year-old male underwent off-pump coronary artery grafting surgery while cerebral function was monitored with bispectral index (BIS). The BIS monitoring was continued into the immediate postoperative period, during which time the patient experienced a cardiopulmonary arrest. The changes in the BIS values helped the resuscitating team in assessing the cerebral response to the cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 13 publications
0
36
1
2
Order By: Relevance
“…The authors concluded that the BIS may be an index of adequate cerebral perfusion during resuscitation. In a case report of cardiac arrest after cardiac surgery, the reduction in blood pressure was accompanied by a parallel drop in the BIS to a value of zero [26]. During the open heart resuscitation, BIS climbed back to the highest value 42 and then this gradually increased to a value of 60 at 15 min after resuscitation.…”
Section: Discussionmentioning
confidence: 97%
“…The authors concluded that the BIS may be an index of adequate cerebral perfusion during resuscitation. In a case report of cardiac arrest after cardiac surgery, the reduction in blood pressure was accompanied by a parallel drop in the BIS to a value of zero [26]. During the open heart resuscitation, BIS climbed back to the highest value 42 and then this gradually increased to a value of 60 at 15 min after resuscitation.…”
Section: Discussionmentioning
confidence: 97%
“…The use of the BIS monitor is frequent during cardiac surgery to help with the titration of the anesthetic. Even though the BIS monitor is not recommended by Aspect Medical as a cerebral ischemia monitor, it has been used by some to assist in resuscitation during CPR [7][8][9]. There are reports to suggest that BIS monitoring during CPR may be helpful not only in ensuring the adequacy of resuscitation, but also effectiveness of changing techniques such as from external chest compressions to open cardiac massage [9].…”
Section: Discussionmentioning
confidence: 98%
“…A low BIS value may be caused by cerebral hypoperfusion [3][4][5][6]. The BIS monitor has also been used to assist medical teams by assessing the adequacy of resuscitative maneuvers during cardiopulmonary resuscitation (CPR) [7][8][9]. However, it has been acknowledged by the manufacturer, Aspect Medical Systems (Norwood, MA, USA), that the BIS is currently not an approved monitor for cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Its ability to detect cerebral hypoperfusion or cerebral ischemia also has been suggested [7]. Previous reports have shown rapid augmentation of BIS after cardiac arrest and successful resuscitation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%